Human resource management in public universities of Vietnam: practices and challenges - Nguyen, Thi Nhai (Đại học Quốc gia Hà Nội, 2020)
Human resource management (HRM) is a strategic element of quality development in universities.The evolution of HRM is, however, slow and certainly challenging inpublic universities of Vietnam. In this paper, we therefore propose to study the HRM models and their practices in Vietnamese public universities. The HRM challenges the public universities are facing are also pointed out in this paper. Last but not least, we raise some discussion questions relating to the choice of HRM models and the necessary policies to support public universities.